MARKET SEGMENTATION STRATEGIES, CHALLENGES FACED AND OVERCOME STRATEGIES IN RURAL INDIAN MARKET - Adsul, Ajit Damodar; Girigisavi, Balwant Dinkar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India's rural market represents a vast and complex consumer base with significant potential for businesses to tap into. However, due to its heterogeneity and socio-economic diversity, market segmentation remains a challenge. This paper explores the basis for rural market segmentation in India, highlights the key segmentation strategies used by marketers, and discusses the implications of demographic, geographic, psychographic, and behavioral segmentation in the rural context. The study also addresses the challenges involved and suggests frameworks for effective segmentation, emphasizing the importance of culturally nuanced, localized approaches.